A Whooping Cough Education Module for WIC Clients in Utah. Issue 5 (September 2017) - Luthy, Karlen E.; Anderson, Alicia; Macintosh, Janelle; Beckstrand, Renea L.; Eden, Lacey M.; Amy, Ryan; Macintosh, Christopher I.
Abstract: Background: Clients in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) are required to complete education modules quarterly to maintain eligibility. The purposes of this project were to: (1) create a whooping cough vaccination education module for WIC clients; (2) evaluate baseline perceptions of WIC clients on the whooping cough vaccine and disease; and (3) evaluate whooping cough knowledge following completion of the module. Problem: A decline in vaccination rates among infants and children using WIC services was reported by a local WIC program director who requested whooping cough vaccination education materials. This quality improvement project included development of a whooping cough education module and evaluation of learning. Methods: Learning was evaluated using a pre- and posttest design. Client feedback was solicited via open-ended questions. Quantitative analysis was performed on visual analog-type questions with paired t -tests and a Cohen's d . Content analysis was conducted on open-ended items. Interventions: The module was designed by a team of vaccination experts and included general definitions, signs and symptoms during the three stages of disease, recommendations to prevent whooping cough, and vaccination recommendations. Learning of users of the module was then evaluated. Results: After using the module, clients indicated they were significantly more likely to vaccinate themselves and their child against whooping cough, and to recommend the vaccination to their family members. The greatest concern of participants about whooping cough was how it affected infants. Participants reported they learned new information on disease seriousness, recognition of symptoms, and treatment options but still requested additional information on the whooping cough disease and vaccine. Conclusions: A whooping cough education module is an effective strategy to improve whooping cough knowledge and promote the whooping cough vaccine. Abstract : Whooping cough can be devastating for babies and children. In this quality improvement project, the authors developed and tested an electronic educational module about whooping cough for women enrolled in the Supplemental Nutrition Program for Women, Infants, and Children in Utah.